Review Paper on the Importance of Usability in Agile Software Development - Butt, Saad Masood; Mazlina, Abdul Majid; Yaqoob, Lubna (Dureesamin Publishers, 2015)
There are many software model are being used in industry like waterfall, rad, and scrum etc. Among all agile model is considered as fastest software development model. In agile, the software development is based on iterative cycle and the main objective is to deliver the software faster with on-going user participation. Traditional software development considered comprehensive feasibility documentation for the success of project where as requirement gathering and comprehensive feasibility report of project are not emphasized in the case of agile software development. Agile model provides rapid solution of software development which leads towards the absence of good design, and architecture and it is observed to be very expensive if followed. As a remedy, a proposed lifecycle for agile software development has been designed. The proposed lifecycle outlined in this paper integrates usability evaluation concepts and agile software methodologies for the development of interactive software. An experimental report will be provided in future after successful testing of proposed lifecycle in the software companies by developing an interactive desktop based application.